DAYA HISAP VACUM CLEANER SEDERHANA - Nurlaili Nurlaili; Bella Veronika; Orizha Cantika; Dona Mustika (Program Studi Pendidikan Fisika FKIP Universitas Samudra, 2018)
A vacuum cleaner is a device that works by using an air pump to create a partial vacuum as a vacuum cleaner and dirt that clings to carpet or on the floor. The workings of a vacuum cleaner are to take advantage of the difference in air pressure, where air will flow at higher air pressure to lower air pressure. The purpose of this study is to make a simple vacuum cleaner with a simple tool that uses a 6 Volt dynamo and 12 volts then calculate the suction power of the vacuum cleaner that was late in making. After testing, the vacuum cleaner that uses a 6 Volt dynamo cannot be used because the accumulator has a voltage of 12 volts greater than the voltage owned by the dynamo so that the current flowing is unbalanced and causes the dynamo to burn and the vacuum cleaner that uses a 12 V dynamo, after it was observed that it had a suction speed of 341,1 × m/s with a suction capacity of 8,67 x